2015
DOI: 10.1007/s00253-015-6841-5
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale chitin extraction from shrimp shell waste by deproteination and decalcification with bacterial enrichment cultures

Abstract: Extraction of chitin from mechanically pre-purified shrimp shells can be achieved by successive NaOH/HCl treatment, protease/HCl treatment or by environmentally friendly fermentation with proteolytic/lactic acid bacteria (LAB). For the last mentioned alternative, scale-up of shrimp shell chitin purification was investigated in 0.25 L (F1), 10 L (F2), and 300 L (F3) fermenters using an anaerobic, chitinase-deficient, proteolytic enrichment culture from ground meat for deproteination and a mixed culture of LAB f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…For example, to produce 1 kilogram of chitosan from shrimp shells, more than 1 tonne of water is need and as well as a large amount of 40% sodium hydroxide solution. Thus, developing a natural way to degrade the waste shells will be promising and necessary 54, 55 . From our results, several chitin degradation-related genes with high expression in the moulting process could be targeted candidates.…”
Section: Resultsmentioning
confidence: 99%
“…For example, to produce 1 kilogram of chitosan from shrimp shells, more than 1 tonne of water is need and as well as a large amount of 40% sodium hydroxide solution. Thus, developing a natural way to degrade the waste shells will be promising and necessary 54, 55 . From our results, several chitin degradation-related genes with high expression in the moulting process could be targeted candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the viscosity of chitosan from low to high effectively increases the respective molecular weight and polymeric chain length [42], which results in potentially greater inter-chain entanglement, hence affecting its viscosity and ability to release the antimicrobial agents. The antimicrobial activity of the formulations will be discussed separately based on the type of agent and chitosan viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, additional substrate feeding in the fed-batch operation might contribute better cell growth and consequently lead the production of various metabolites (Abou-taleb 2015). It was also reported that change in alkalinity was caused due to breakage of peptide linkages of chitin by proteolysis (Bajaj et al 2016), and high demineralization rate was found at pH 5.86 during the batch degradation of chitin (Ghorbel-Bellaaj et al 2011). GlcNAc was reported to result from the chitin degradation optimally at pH 5.3 (Chen et al 2010).…”
Section: Changes In Cell Density and Phmentioning
confidence: 99%